An Efficient Method for the Conjugation of Hydrophilic and Hydrophobic Components by Solid‐Phase‐Assisted Disulfide Ligation. (19th January 2018) - Muguruma, Kyohei; Shirasaka, Takuya; Akiyama, Daichi; Fukumoto, Kentarou; Taguchi, Akihiro; Takayama, Kentaro; Taniguchi, Atsuhiko; Hayashi, Yoshio
Abstract: Chemical conjugation between hydrophilic and hydrophobic components is difficult because of their extremely different solubility. Herein, we report a new versatile method with a solid‐phase‐assisted disulfide ligation to overcome the difficulty of conjugation attributed to solubility. The method involves two steps in a one‐pot process: 1) loading of a hydrophobic molecule onto a resin in an organic solvent, and 2) release of the solid‐supported hydrophobic molecule as a conjugate with a hydrophilic molecule into an aqueous solvent. This strategy allows the use of a suitable solvent system for the substrates in each step. Conjugates of a water‐insoluble drug, plinabulin, with hydrophilic carriers that could not be prepared by solution‐phase reactions were obtained in moderate yields (29–45 %). This strategy is widely applicable to the conjugation of compounds with solubility problems.